Insight into improved thermostability of cold-adapted Staphylococcal Lipase by glycine to cysteine mutation - Veno, Jiivittha; Raja Noor Zaliha, R. A. R.; Masomian, Malihe *; Mohd Shukri MA,; Nor Hafizah AK, (MDPI, 2019)
Thermostability remains one of the most desirable traits in many lipases. Numerous studies have revealed promising strategies to improve thermostability and random mutagenesis often leads to unexpected yet interesting findings in engineering stability. Previously, the thermostability of C-terminal truncated cold-adapted lipase from Staphylococcus epidermidis AT2 (rT-M386) was markedly enhanced by directed evolution. The newly evolved mutant, G210C, demonstrated an optimal temperature shift from 25 to 45 ◦C and stability up to 50 ◦C. Interestingly, a cysteine residue was randomly introduced on the loop connecting the two lids and accounted for the only cysteine found in the lipase. We further investigated the structural and mechanistic insights that could possibly cause the significant temperature shift. Both rT-M386 and G210C were modeled and simulated at 25 ◦C and 50 ◦C. The results clearly portrayed the effect of cysteine substitution primarily on the lid stability. Comparative molecular dynamics simulation analysis revealed that G210C exhibited greater stability than the wild-type at high temperature simulation. The compactness of the G210C lipase structure increased at 50 ◦C and resulted in enhanced rigidity hence stability. This observation is supported by the improved and stronger non-covalent interactions formed in the protein structure. Our findings suggest that the introduction of a single cysteine residue at the lid region of cold-adapted lipase may result in unexpected increased in thermostability, thus this approach could serve as one of the thermostabilization strategies in engineering lipase stability.